The Crucial Role of Court Proceedings Reports in Criminal Case Proceedings and the Dilemma of Judicial Decision-Making - Bakhrul Amal (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The impact of legal positivism on law enforcement has been substantial. Judges, when deciding a case, consistently adhere to the indictment presented by the public prosecutor, even though at times the indictment may conflict with the facts presented during the trial. In such instances, the role of the court session report in the trial process seems to be merely that of a record rather than a factual account. This research aims to examine the position of the court session report in criminal case proceedings and whether it can serve as a basis for a judge's decision outside the scope of the indictment, particularly when the contents of the indictment differ from the proven facts in court. This article finds out that the status of the court session report as a basis for evidence is deemed equally significant as the position of the indictment prepared by the public prosecutor. For this reason, the judge may consider the court session report as a source for deciding a criminal case brought before them.